Evaluation of Lipid Profile as Indicators for Patients with Erectile Dysfunction - Hayder Hamed Abed; Muthanna I. Al-Ezzi (College of Pharmacy / Mustansiriyah University, 2011)
Patients with cardiovascular diseases or erectile dysfunction initially present to primary care physicians, who have an opportunity to intervene early and favorably affect the clinical course of either condition. Recognition and aggressive treatment of cardiovascular disease risk factors has a major role in management of cardiovascular disease and erectile dysfunction. Twenty Iraqi patients with age range of 45-50 years were considered in this study. The evaluation of erectile dysfunction was according to NIH Consensus Development Panel on Impotence Procedure. The NIH provided complete information about severity of erectile dysfunction by using its questionnaire. The lipid profile was performed individually. The obtained results predicted elevation of all lipid profile parameters. The results were as follow: Cholesterol 6.65±0.27 mmol/L, triacylglyceral 5.93±0.22 mmol/L, LDL-cholesterol 4.424 ± 0.28 mmol/L, VLDL 1.19 ±0.18 mmol/L and HDL 1.04 mmol/L. All collected results showed strong evidence between increased on serum lipids and erectile dysfunction and laboratory evaluation of lipid showed performed to patients with erectile dysfunction.